Identifying the Contributions of Mother Language to the Sustainable Development of Bangladesh - Momen, Abdul (Mother Language, 2025)
As the mother tongue of Bangladesh, Bengali (Bangla) serves not only as a representation of the country’s cultural identity but also as a driving force behind sustained economic growth. Examining the myriad ways in which Bengali has contributed to the advancement of the nation. This paper focuses on four primary areas: enhancing educational outcomes through instruction in the mother tongue, promoting economic inclusion in agriculture, small and medium enterprises (SMEs), and the gig economy; strengthening cultural resilience in the face of globalization; and enabling digital adaptation through the implementation of technological solutions that are tailored to the local environment. The study highlights the vital role that Bengali plays in improving inclusive education (SDG 4), eliminating social and economic inequities (SDG 10), and fostering decent employment and economic growth (SDG 8). The study uses a qualitative methodology based on historical analysis and contemporary observation. The findings support the implementation of policy frameworks that prioritize schooling in the mother tongue, accessibility to digital resources, and cultural preservation as essential components in achieving sustainable development while simultaneously protecting linguistic heritage. Mother Language, 2025; 9(1): 5-43